Gastric perforation presenting as bilateral scrotal pneumatoceles - Aslan, Yakup; Sarıhan, Haluk; Dinç, Hasan; Gedik, Yusuf; Aksoy, Ayşe; Dereci, Selim (The Turkish Journal of Pediatrics, 1999)
Although processus vaginalis is patent in the majority of newborn infants, the expression of an intraabdominal pathology such as gastrointestinal perforation or bleeding in the scrotum is very rare. In a large percentage of neonates with the gastrointestinal perforation, pneumoperitoneum is absent. In any case, it may not be detected in early radiographs. We report a newborn baby who presented with bilateral scrotal pneumatoceles as a first sign of pneumoperitoneum due to gastric perforation. Plain x-ray of the abdomen was normal except for pneumoscrotum, but contrast study revealed gastric perforation.
Keywords: gastric perforation; scrotal pneumatocele